Systematic screening and focused evaluation for veno-occlusive disease/sinusoidal obstructive syndrome (VOD/SOS) following allogeneic stem cell transplant is associated with earlier diagnosis and prompt institution of defibrotide treatment - Avenoso, Daniele; Kenyon, Michelle; Mehra, Varun; Krishnamurthy, Pramila; Kulasekararaj, Austin; Gandhi, Shreyans; Dazzi, Francesco; Naresh Shah, Mili; Wood, Henry; Leung, Ye Ting; Eaton, Alicia; Anteh, Sandra; et al. (Frontiers in Transplantation, 2022)
The sinusoidal obstructive syndrome (SOS), also known as hepatic veno-occlusive disease (VOD), is a potentially life-threatening complication following haemopoietic stem-cell transplantation. The availability of reduced intensity conditioning regimens and new drugs for malignant haematological conditions allowed more patients to be eligible for allogeneic haematopoietic stem cell transplant. This translates in transplant patients with multiple risk factors for VOD/SOS. Based on these considerations, we have undertaken a dedicated weekly VOD/SOS ward round which aims to facilitate early diagnosis of VOD/SOS and pre-emptively identify patients at risk, where a careful evaluation of differential diagnosis is essential. Herein, we present the results of our VOD-ward round; between September 2020 and April 2022, 110 consecutive patients have been evaluated with a focused VOD-ward round.108out of 110patients underwent HSCT with at least one known risk factor for developing VOD/SOS. The median number of risk factors present in the VOD/SOS group and non-VOD/SOS group were 5(range 3 – 6)and 3(range 0 – 7),respectively.Late onset VOD/SOS was diagnosed in 45% of our patients.The early identification of patients with multiple risk factors for VOD/SOS allowed the diagnosis of the complication before the onset of multiorgan failure and we were able to decrease the median time to treatment by 48 hours.